E-Learning at the university during the covid-19 pandemic, between perspectives and reality on the ground - Ayad, Abla (Journal of Human Sciences, 2022)
With the health crisis of Covid-19, E-Learning has become the focus of interest of various educational institutions, particularly the university. In Algeria, like many countries in the world, the Ministry of Higher Education and Scientific Research opted for a hybrid education, during the academic year 2020-2021 to fight against the spread of the virus. In this context, the teaching takes place in two alternatives, a period of face-to-face teaching, followed by a period of distance learning. To ensure pedagogical support for the learners during the distance learning phase, it was recommended that teachers provide online sessions via the MOODLE platform or other devices. Through this contribution, we plan to highlight the different teaching/learning strategies generated by this mode of teaching. We also wonder about its effectiveness and we hope to propose resolutions that would contribute to its improvement.